2015
DOI: 10.1111/zoj.12214
|View full text |Cite
|
Sign up to set email alerts
|

Integrative systematics of northern and Arctic nudibranchs of the genusDendronotus(Mollusca, Gastropoda), with descriptions of three new species

Abstract: The taxonomy of common northern nudibranch molluscs of the genus Dendronotus in the vast cold regions of Eurasia remains largely unknown. Abundant material collected in many localities from the Barents Sea, via the Arctic region, to the north-west Pacific was analysed for the first time. An integrated approach combining morphological and ontogenetic data with molecular four-gene (COI, 16S, H3, and 28S) analysis reveals seven species, including three previously undescribed. Dendronotus frondosus (Ascanius, 1774… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 46 publications
6
68
2
Order By: Relevance
“…Stout et al (2010: 7) also suggested that “Further examination of additional specimens from various locations may reveal a complex of species currently considered to be Dendronotus frondosus .” This was fulfilled in a recent revision of the genus Dendronotus by Ekimova et al (2015). In this study two new species ( Dendronotus kalikal Ekimova, Korshunova, Schepetov, Neretina, Sanamyan & Martynov, 2015 and Dendronotus kamchaticus Ekimova, Korshunova, Schepetov, Neretina, Sanamyan & Martynov, 2015) were described from the northwestern Pacific Kamchatka waters, both of which are very similar externally to Dendronotus frondosus .…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Stout et al (2010: 7) also suggested that “Further examination of additional specimens from various locations may reveal a complex of species currently considered to be Dendronotus frondosus .” This was fulfilled in a recent revision of the genus Dendronotus by Ekimova et al (2015). In this study two new species ( Dendronotus kalikal Ekimova, Korshunova, Schepetov, Neretina, Sanamyan & Martynov, 2015 and Dendronotus kamchaticus Ekimova, Korshunova, Schepetov, Neretina, Sanamyan & Martynov, 2015) were described from the northwestern Pacific Kamchatka waters, both of which are very similar externally to Dendronotus frondosus .…”
Section: Introductionmentioning
confidence: 57%
“…Using a combination of external and internal morphological characters, Dendronotus arcticus sp. n. can be distinguished from all recently reviewed species of the genus Dendronotus (Stout et al 2010, Ekimova et al 2015, Martynov et al 2015a, b). The molecular data also support the description of Dendronotus arcticus sp.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations